Potency and Stability Emulgel of Ethanol Extract Strawberry Leaf (Fragaria x ananassa var Duchesne) as a Sunscreen - Detyari Faza Auliya; Hery Muhamad Ansory; Suhartinah Suhartinah (Majalah Farmaseutik, 2022)
Strawberry leaf extract (Fragaria x ananassa var Duchesne) was reported to have good sunscreen activity. A good dosage formulation is necessary for the next stage. The purpose of this study was to formulate emulgel from the ethanol extract of strawberry leaves using physical quality tests, stability tests, and SPF value test.                 The strawberry leaves were extracted by the reflux method using 96% ethanol as solvent. The extract was analyzed for chemical content by TLC. The emulgel preparation is formulated with a concentration of 0,25%; 0,50% and 1%. The preparations were tested for physical quality, stability, and sunscreen activity using in vitro and in vivo. In vitro test using UV-Vis spectrophotometry and in vivo with experiments on human skin.The results showed that the yield of ethanol extract of strawberry leaves was 20,5% and the TLC test showed positive content of flavonoids and tannins. The emulgel formula had the best effectiveness as a barrier was formula with an extract concentration of 1%. The 1% ethanol extract concentration of strawberry leaves an emulgel resulted in SPF value of 59,94 ± 0,260.